Association mapping analysis for cultivated and weedy types of Perilla crop collected from South Korea using morphological characteristics and SSR markers - So Jung Jang; Kyu Jin Sa; Zhen Yu Fu; Ju Kyong Lee (Heliyon, 2024)
There are two cultivated and weedy types of Perilla crop (TCWTPC), and they are widely distributed and cultivated in East Asia, especially in South Korea and Japan. The objective of this study is to create simple sequence repeat (SSR) markers linked to morphological traits that show differences between accessions of the TCWTPC using recently designed SSR primer sets in Perilla crop. Genetic diversity within 52 accessions of the TCWTPC, gathered from South Korea, was assessed using 28 novel Perilla SSR primer sets. Based on the assessment, a collection of 28 Perilla SSR primer sets were shown to exhibit polymorphism and yielded a total of 142 alleles across the 52 accessions of the TCWTPC. Through inspection of a phylogenetic tree and population structure, the 52 accessions of the TCWTPC were classified into three major groups. Although most accessions of the TCWTPC were relatively clearly distinguished, SSR markers failed to distinguish several accessions belonging to the two weedy types of the Perilla crop. By using an association mapping analysis (AMA) of the 28 Perilla SSR markers and seven morphological characteristics in the 52 TCWTPC accessions, we detected that three of the Perilla SSR markers (KNUPF134, KNUPF137, KNUPF149) were associated with plant and seed characteristics. The novel SSR primer sets developed in Perilla crop should be useful in AMA for assessing genetic diversity and relationships between and within TCWTPC accessions, and this information will be helpful for genetic mapping in breeding programs for Perilla crop.